HABITAT ASSOCIATIONS OF ANT SPECIES (SUBFAMILY: MYRMICINAE) IN A HETEROGENEOUS LANDSCAPE OF KALABURAGI DISTRICT, KARNATAKA - BEGUM, RABIYA; MAJAGI, SHASHIKANTH H.; VIJAYKUMAR, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
The present study analyzes the variations in ants' community, especially with the myrmicinae group studied with respect to human, vegetative, dry land, and teak plantation habitats. The species richness remains the same in both human and vegetative habitats, while the abundance was high in vegetative habitat. The Simpson index (1-D) for human (social) and vegetative habitats was 0.6274 and 0.3706, respectively, which is less than 1, indicating a low diversity regarding the myrmicinae in these habitats. However, Shannon Wiener index (H) was 1.398 and 0.8349 for both human and vegetative habitats, indicating the more no. of species quartered in humans compared to vegetative habitats. Solenopsis germinata, the only species encountered in the dry land habitat, surprisingly, no ants belonging to myrmicinae were captured in the teak plantation. These preliminary results define the effects of different land-use patterns and illustrate ants' sensibility to changing landscape and disturbance due to various anthropogenic activities, which encourages their inclusion of species-level interactions within the habitat in conservation orientated bio-monitoring.